Perfomance appraisal system and its effect on effort, job perfomance and development : Individuals perception in Malaysian Civil Service - Azila binti Ayob (Kulliyyah of Islamic Revealed Knowledge, International Islamic University Malaysia, 2009)
Performance appraisal is an important tool in human resource management because through performance appraisal an organization can identify the potential of its human resources that can help advance the success of the organization in achieving its goals and at the same time could help in making decisions relating to pay, promotion and training needs in a fair and accurate way. The current performance appraisal system was first introduced in the Malaysian civil service under the New Remuneration System (NRS) in 1992 through the Management by Objectives system. This system is result oriented where the evaluation is based on the achievement of work targets that have been predetermined by the employees with their managers. The system is applied to all civil service employees in order to enhance their efficiency and to reward them based on performance. Thus, this study measures the perception of the civil service employees towards the effect of such a performance appraisal system in enhancing their effort, job performance and development among individuals. Survey questionnaires were used for this purpose and were distributed to a random sample of employees in three civil service departments. This study reviews the accuracy of the appraisal system and finds the employees believe that the rates given are accurate. The accuracy of the system has shown to have an effect in enhancing their effort and motivation to perform better. The employees also believe that procedural justice exists in the system. Their perception of the fairness in implementation of the system has created a moderate link to enhance effort and performance. The study also found that the employees consider the rewards offered for excellent performance are worth their effort and are valuable which makes the employees feel motivated to increase their effort to achieve a high performance. The performance appraisal system in the Malaysian civil service also has shown its developmental aspect where most of the respondents believe that the system helps in career development in that the system can identify their strengths and weaknesses. It could also determine the appropriate training needed by them. The system provides a channel for them to have communication with their managers in discussing their potentialities in their career. Therefore, the developmental aspects have a very strong effect in affecting their effort to increase their performance. Some suggestions for improvement of the current performance appraisal system are made by this research.